Metode Multi Attribute Utility Theory (MAUT) dalam Keputusan Pengendalian Persediaan Obat dan Alat Kesehatan - Puspita, Retchi (Jurnal Informatika Ekonomi Bisnis, 2022)
Medicines and medical devices are one of the most important parts of a health service, so it is necessary to guarantee the availability of drugs and medical devices for treatment so that the process can run effectively and efficiently. The shortage of medicines and medical devices is a significant public health problem, especially for medicines and medical devices associated with life-threatening conditions. Meanwhile, inventory that is too large will increase investment funds and increase risks such as loss, expiration and damage to drugs. For this reason, this study aims to make decisions on controlling the supply of drugs and medical devices so that they can be guaranteed in sufficient quantities by supporting decisions using the MAUT method. The data used in this study is the amount of inventory that runs out per day, per week, per month and a lot of inventory per day, per week, per month. The results of this study are expected that the Multi Attribute Utility Theory (MAUT) method can assist pharmacists in making decisions on controlling drug supplies and medical devices very well. So this research is very appropriate in controlling the supply of drugs and medical devices in pharmacies.